HUBUNGAN INTENSITAS PENGGUNAAN MEDIA SOSIAL DENGAN TINGKAT REGULASI EMOSI PADA REMAJA DI SMK NEGERI 2 MEDAN: THE RELATIONSHIP BETWEEN THE INTENSITY OF SOCIAL MEDIA USE AND THE LEVEL OF EMOTIONAL REGULATION AMONG ADOLESCENTS AT SMK NEGERI 2 MEDAN - Selia Nazila; Meri Susanti; Bania Maulina; Selly Oktaria (Jurnal Kedokteran STM (Sains dan Teknologi Medik), 2026)
The use of social media among adolescents continues to increase and may influence psychological conditions, including the ability to regulate emotions. Exposure to negative content, social comparison, and high intensity of use may affect adolescents’ emotional regulation abilities. This study aimed to determine the relationship between the intensity of social media use and the level of emotional regulation among adolescents at SMK Negeri 2 Medan in 2025. This research employed a quantitative analytic method with a cross-sectional design. The sample consisted of adolescents aged 15–18 years selected using purposive sampling. Data were collected using the Social Media Use Integration Scale (SMUIS) to measure the intensity of social media use and the Emotion Regulation Questionnaire (ERQ) to assess emotional regulation. Data were analyzed using the Pearson correlation test. The results showed that the majority of respondents were male adolescents. The intensity of social media use was categorized as high, while the level of emotional regulation was categorized as low. Statistical analysis indicated that there was no significant relationship between the intensity of social media use and emotional regulation (p = 0.096; p > 0.05), with a correlation coefficient of r = 0.171, indicating a very weak positive relationship. In conclusion, there was a very weak positive relationship between the intensity of social media use and emotional regulation among adolescents at SMK Negeri 2 Medan; however, the relationship was not statistically significant. AbstrakPenggunaan media sosial pada remaja semakin meningkat dan berpotensi memengaruhi kondisi psikologis, termasuk kemampuan dalam mengatur emosi. Paparan konten negatif, perbandingan sosial, serta intensitas penggunaan yang tinggi dapat berdampak pada kemampuan regulasi emosi remaja. Penelitian ini bertujuan untuk mengetahui hubungan antara intensitas penggunaan media sosial dengan tingkat regulasi emosi pada remaja di SMK Negeri 2 Medan tahun 2025. Penelitian ini menggunakan metode kuantitatif dengan pendekatan analitik dan desain cross sectional. Sampel terdiri dari remaja berusia 15–18 tahun yang dipilih menggunakan teknik purposive sampling. Pengumpulan data dilakukan menggunakan kuesioner Social Media Use Integration Scale (SMUIS) untuk mengukur intensitas penggunaan media sosial dan Emotion Regulation Questionnaire (ERQ) untuk mengukur regulasi emosi. Analisis data menggunakan uji korelasi Pearson. Hasil penelitian menunjukkan bahwa mayoritas responden berjenis kelamin laki-laki. Intensitas penggunaan media sosial berada pada kategori tinggi, sedangkan tingkat regulasi emosi berada pada kategori rendah. Hasil analisis menunjukkan tidak terdapat hubungan yang signifikan antara intensitas penggunaan media sosial dengan regulasi emosi (p = 0,096; p > 0,05) dengan nilai koefisien korelasi r = 0,171 yang menunjukkan hubungan positif dengan tingkat kekuatan sangat lemah. Kesimpulannya, terdapat hubungan positif dengan tingkat kekuatan sangat lemah antara intensitas penggunaan media sosial dengan regulasi emosi pada remaja di SMK Negeri 2 Medan, namun hubungan tersebut tidak signifikan secara statistik.